Liveability aspirations and realities: Implementation of urban policies designed to create healthy cities in Australia. (January 2020) - Lowe, Melanie; Arundel, Jonathan; Hooper, Paula; Rozek, Julianna; Higgs, Carl; Roberts, Rebecca; Giles-Corti, Billie
Abstract: Creating healthy, liveable cities is a common policy aspiration globally. However, little research has explored the capacity of urban policies to deliver this aspiration, or levels of policy implementation. This study aimed to develop policy-relevant indicators, to detect within- and between-city inequities in the implementation of Australian state government policy targets related to urban liveability. Seventy-three government policies were reviewed across Australia's four largest cities to identify measurable spatial policies that contribute to creating healthy, liveable neighbourhoods. Spatial indicators based on these policies were developed to assess and map levels of policy implementation at the metropolitan and sub-metropolitan level. Measurable spatial policies were identified for only three out of seven policy domains: walkability, transit access, and public open space. While there was significant variation between cities, policies were often inconsistent with evidence about how to achieve liveability. No Australian city performed well on all liveability domains. Even modest policy targets were often not achieved, and there were significant spatial inequities in policy implementation. With few exceptions, people living in outer suburbs had poorer access to amenities than inner-city residents. This study demonstrates the benefits and challenges of measuring urban policy implementation. Evidence-informed targets are needed in urban, transport and infrastructure policies designed to create healthy, liveable cities, to enable levels of (and inequities in) policy implementation to be assessed. Consistent standards for government spatial data would enable development of comparable indicators and cities to be directly compared. Highlights: Liveability indicators assessed implementation of Australian urban policy. Policies were often inconsistent with evidence about how to achieve healthy cities. Indicators showed policy implementation gaps and spatial inequities within cities. Outer suburbs had poorer access to amenities than inner-city areas.